2014
DOI: 10.1590/s0100-40422014000100012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and application of ion imprinted poly(vinylimidazole) for zinc ion extraction/preconcentration with faas determination

Abstract: In this paper, we describe the synthesis of an ion imprinted polymer (IIP) by homogeneous polymerization and its use in solid-phase to extract and preconcentrate zinc ions. Under optimal conditions (pH 5.0, preconcentration flow rate of 12.0 mL min -1 , and eluted with 1.0 mol L −1 HNO 3 ) this procedure allows the determination of zinc with an enrichment factor of 10.2, and with limits of detection and quantification of 1.5 and 5.0 μg L −1 , respectively. The accuracy of our results was confirmed by analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…The rougher surface was attributed to the binding occurred, resulting in cavities when the template was removed (González et al, 2006). A few similar observations were also reported, which were attributed to the differences in surface morphology between the imprinted polymer and the NIPs (Ahamed et al, 2013;Santos et al, 2014;Sikiti et al, 2014) studied by SEM. Next, the FTIR studies showed that both Py-IP and NIP had similar backbone, due to the similar functional monomer used.…”
Section: Discussionmentioning
confidence: 61%
“…The rougher surface was attributed to the binding occurred, resulting in cavities when the template was removed (González et al, 2006). A few similar observations were also reported, which were attributed to the differences in surface morphology between the imprinted polymer and the NIPs (Ahamed et al, 2013;Santos et al, 2014;Sikiti et al, 2014) studied by SEM. Next, the FTIR studies showed that both Py-IP and NIP had similar backbone, due to the similar functional monomer used.…”
Section: Discussionmentioning
confidence: 61%
“…The lower intensity peak observed at 1630 cm −1 can be assigned to OH deformation (water) or C = C stretching from vinyl groups [27]. The angular out-of-plane deformation of the methyl groups is verified by the band at 1386 cm −1 [28] and those verified at 960 and 760 are assigned to the C-H (imidazole ring) bending out-of-plane [29].…”
Section: Characterization Of the Pvi And Pma Polymers By Ft-ir Sem mentioning
confidence: 91%
“…The absorption at 962 and 765 cm -1 is assigned to the C-H (ring) bending outof-plane [33,34]. The peak at 1380 cm -1 is attributed to C=N stretching modes from the ring [21]. The strong and broad absorption bands around 3700-3100 cm -1 correspond to water O-H stretching.…”
Section: Ft-ir Spectramentioning
confidence: 99%
“…Introduction samples [18][19][20][21][22]. Biosorption of zinc(II) ion from water using ion-imprinted interpenetrating polymer network was investigated by Girija and Beena [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation